Quest for an Innovative Methodology for Retrofitting Urban Built Heritage: An Assessment of Some Historic Buildings in Kano Metropolis, Nigeria - Danjuma Abdu Yusuf; Abubakar Ahmed; Jie Zhu; Abdullahi M. Usman; Musa S. Gajale; Shihao Zhang; Jiang Jialong; Jamila U. Hussain; Abdullahi T. Zakari; Abdulfatah Abdu Yusuf (Buildings, 2023)
Historical buildings have inhabited every epoch of history. Some of these built legacies are now in ruins and dying whilst others are somewhat undamaged. Knowledge of conservation techniques available today has allowed us to understand more innovative ways of conserving the built heritage. Such techniques are, however, incompatible with the building materials available in our historical epoch and environment. People seek to reclaim the forgotten cultural heritage in the midst of the heritage conservation era while bearing in mind that previous work seldom takes into account the inventive preservation methods of today. This study aims to explore the innovative built heritage conservation practice in the Kano metropolis, to detect deterioration and incorporate traditional wisdom and contemporary innovation according to modern urban development. The study adopted qualitative research with a descriptive approach. The descriptive research explains, examines, and interprets prevailing practices, existing situations, attitudes, reasons, and on-going processes, while the qualitative research approach uses spatial analysis methods (direct assessment of physical characteristics of the selected buildings) and focus group discussion (FGD) sessions with the custodians, prominent elderly persons, or ward head (Mai Unguwa) from each of the selected buildings. In this work, we found it necessary to survey 29 historical buildings of which three of the historic buildings from pre-colonial, colonial, and post-colonial architecture were purposively sampled for inclusion. This is on the basis of their value formation, processes, phenomena, and typology. The findings reveal that deterioration is due to decaying plaster and paint, moist walls, deformed openings, sagging roofs, wall cracks, roof leakages, exit spouts, stains, and corrosion. Other factors include microbes and termite attacks, inappropriate use and neglect, civilization, and inappropriate funding. Conservation was performed to avert the amount of decay while the techniques in practice are documentation methods and treatment interventions with no implementation of diagnostic methods. It further unveils the potential benefits of local treatment, as evidenced by the intervention at the Dorayi palace segment, the use of “makuba” (milled locust bean pod) to stabilize the geotechnical performance of “tubali” (local mud bricks) to improve its potency. This milled locust bean pod also serves as the water repellent consolidant in “laso” (local) plaster, which has proven to be eco-friendly, non-toxic, and effective in wall rendering. The need for immediate implementation of diagnosis techniques in the conservation of architectural heritage in the municipality and elsewhere in Nigeria and beyond is eminent. Intervention and implementation of policies, appropriate funding, and mobilization, raising awareness and sensitization on the value, significance, and state of affairs of our cultural heritage is also paramount.